Organizational Identity and Learning: A Psychodynamic Perspective - Brown, Andrew D.; Starkey, Ken (Academy of Management Review, 2000)
Organizations are prone to ego defenses, such as denial, rationalization, idealization, fantasy, and symbolization, that maintain collective self-esteem and the continuity of existing identity. These defenses are dysfunctional when they militate against necessary organizational change. Maladaptive identity defense mechanisms can be mitigated through processes of organizational learning in the form of critical self-reflexivity and an identity-focused dialogue, which promote attitudes of wisdom.